ASSESSING THE APPLICATION OF SECURITISATION IN LITHUANIA - Miškinis, Algirdas; Čipkutė, Eivilė (Ekonomika, 2012)
The aim of this article is to analyse the application possibilities of the securitisation mechanism in Lithuania. Securitisation has been used for a few decades by banks as an instrument to decrease credit risk and broaden the sources of funding. The increasing demand for asset-backed securities has prompted the development of this mechanism. Nevertheless, despite its benefits, if used irresponsibly, this mechanism can also create risks to financial stability. Foreign capital banks dominate in the Lithuanian banking sector, and their financing structure is highly based on parent bank loans, which is the second largest financing source after deposits. As the recent economic crises have shown, the flow of this resource is unstable and pro-cyclical. Therefore, banks ought to seek additional funding sources. The issue of securities backed by bank loans could be one of those sources. The authors of this article, with the help of regression analysis, have assessed a possible effect of additional credit flow, which could be attracted by banks using securitisation, on country’s GDP. The analysis has shown that certain types of loans can significantly impact the country’s GDP growth. The most significant effect on GDP would be reached, if banks would securitize new loans issued to households and use the obtained funds to issue more loans to households.